Anonymous
Anonymous asked in Science & MathematicsMathematics · 4 weeks ago

Solve the system by elimination?

{3a+4b=9

{-3a-2b=-3

12 Answers

Relevance
  • 4 weeks ago

    3a+4b=9------(1)

    -3a-2b=-3-----(2)

    (1)+(2)=>

    2b=6=>

    b=3

    (1)+2*(2)=>

    -3a=3=>

    a=-1

    The answer is

    a=-1

    b=3

  • 4 weeks ago

    First add the two equations to eliminate the variable "a."

    3a + 4b = 9

    -3a-2b =-3

    ----------------

    2b = 6

    b=3

    Now, substitute the value of "b' into either equation.

    3a + 4(3) = 9

    3a = 9-12    (Subtract 4(3) = 12 from both sides of the equation.)

    3a = -3

    a= -1

    Answer (a, b) = ( -1, 3)

  • 4 weeks ago

    Subtract the two equations. This will eliminate 'a' 

    Hence 

    2b = 6 

    b = 3 

    When b = 3 

    3a + 4(3) = 9 

    3a + 12 = 9 

    3a = -3 

    a = -1 

  • Philip
    Lv 6
    4 weeks ago

     3a+4b =  9...(1).;

    -3a-2b = -3...(2).;

    (1)--->3a=9-4b;

    Substitute (9-4b) for the 3a in (2) getting -(9-4b)-2b = -3;

    ie., 9-4b+2b=3;

    ie., 9-2b=3;

    ie., 2b=9-3 = 6;

    ie., b = 3;

    Then (1)---> 3a = 9-12 = -3;

    ie., a = -1.;

  • How do you think about the answers? You can sign in to vote the answer.
  • 4 weeks ago

    (1) : 3a + 4b = 9

    (2) : - 3a - 2b = - 3

    You calculate (1) + (2)

    (3a + 4b) + (- 3a - 2b) = 9 + (- 3)

    3a + 4b - 3a - 2b = 9 - 3

    2b = 6

    → b = 3

    Recall (1) : 3a + 4b = 9

    3a = 9 - 4b → where: b = 3

    3a = - 3

    → a = - 1

  • 4 weeks ago

    3A+4B=9, 3A+2B=3

    subtract>>0A+2B=6, B=3, A=-1

  • 4 weeks ago

    3a + 4b = 9

    -3a - 2b = -3

    2b = 6

    b = 3

    a = -1

  • Anonymous
    4 weeks ago

    Surprising how many people get their education on Yahoo! Answers. Could be why the world is so screwed up nowadays.If you can't cook, get out of the kitchen.

    Attachment image
  • 4 weeks ago

    {3a+4b=9 ... eq1

    {-3a-2b=-3 .. eq2

    ----------------

        2b = 6

      b = 3  Answer//

    solving for a from eq1

    3a  + 4b = 9

    3a + 4(3) = 9

    3a + 12 = 9

     3a = 9 - 12

    3a = - 3

     a = - 1  answer//

  • 4 weeks ago

    Add the equations:

    2b = 6, so b = 6/2 = 3

    Multiply the second equation by 2:

    -6a - 4b = -6

    Add that to the first equation:

    -3a = 3

    a = 3/(-3) = -1

Still have questions? Get your answers by asking now.